Recent Development in LiFePO4 Surface Modifications with Carbon Coating from Originated Metal-Organic Frameworks (MOFs) to Improve the Conductivity of Cathode for Lithium-Ion Batteries: A Review and Bibliometrics Analysis - Apang Djafar Shieddieque; Iman Rahayu; Sahrul Hidayat; Joddy Arya Laksmono (Universitas Muhammadiyah Magelang, 2023)
Using lithium-ion batteries has emerged as a viable approach to lessen the negative effects of fossil fuel use. LiFePO4 (LFP) is one of the lithium-ion batteries that are eco-friendly and safer than others. However, LFP has a main limitation with the poor rate performance due to its low electronic conductivity number. This study aims to present a bibliometric review of the analysis using VOSviewer of surface modification using carbon coating of metal-organic frameworks (MOFs) to improve the challenge of synthesis, structure, electrochemical stability, and performance of LFP. The results of this study showed that surface modification of LiFePO4 electrodes using carbon compounds produced from MOFs improved the efficiency of electrochemical energy storage and conversion technologies. High levels of porosity and customizable characteristics are offered by metal-organic frameworks (MOFs) ideal for surface modification which improves the battery conductivity. The bibliometric analysis showed that research on lithium-ion batteries is currently receiving attention, a sign of its significance and rising popularity. It is suggested for researchers especially Indonesian researchers to contribute more to this field.